Surgical site infection in reconstructive and aesthetic breast surgery: A single center retrospective analysis of the association between healthcare workers and infections. Issue 11 (November 2022) - Kracoff, Sharon; Berl, Ariel; Allweis, Tanir M.; Egozi, Dana
Summary: Background: Reconstructive and aesthetic breast surgeries are frequently performed procedures, and the consequences of a postoperative infection are devastating both for the patient and the healthcare (HC) system. Over the years, there has been heightened interest in the physical and mental well-being of physicians and HC workers. Little is known about the relationship between HC workers and surgical site infections (SSI), and whether HC workers are at an increased risk for SSI. The aim of this study was to investigate whether women working in the HC system have an increased risk for SSI following reconstructive and aesthetic breast surgery. Materials and methods: We conducted a retrospective analysis of all patients who underwent aesthetic and reconstructive breast surgery at our institution between the years 2013–2020. Women who were recognized as HC workers were analyzed in a separate group and compared to those who were not. Results: Records of 378 patients were reviewed, of whom 53 (14%) were identified as HC workers. The overall infection rate was 17.4%. HC workers manifested a higher infection rate than the other group (32% vs. 15.1%, p<0.05) and a significantly higher relative risk for SSI (RR 2.12, p<0.01). Conclusions: Women working in the HC system may have an increased risk of developing postoperative infectious complications following aesthetic and reconstructive breast-related surgery. Further research is needed to corroborate these findings and elucidate the causes.